A Stage-by-Stage Assessment of Enterprise Resource Planning Implementation: An Empirical Study from Hong Kong. Issue 2 (2nd April 2016) - Sun, Hongyi; Ni, Wenbin; Lam, Rocky; Ng, Chun Yi
ABSTRACT: An enterprise resource planning implementation lifecycle model consists of several stages. The outcome of one stage becomes the starting conditions of the subsequent stage. Therefore, a milestone performance assessment at each stage is needed to ensure the successful implementation of the subsequent stages, which is not presented in current literature. Why a previous stage is important to the next one and what role it plays during enterprise resource planning implementation lacks substantial evidence. This article reports the development and validation of a stage-by-stage lifecycle assessment model for enterprise resource planning implementation based on a survey and structural equation modeling. Critical success factors of enterprise resource planning implementation are systematically associated with enterprise resource planning lifecycle stages, and key performance indicators of each critical success factor is developed to measure the performance of enterprise resource planning stages. The model is empirically tested with data from Hong Kong manufacturing firms. The research demonstrates the performance of one stage does affect those of its following stages. The results are discussed and their implications are explored.